The tectonic features of the Sabana de Bogotá region and formation mechanisms of structures (1963)
The Sabanas region, in the Colombian “Cordillera Oriental”, is a region characterized not only by the presence of important quaternarian lacustrine puddings, which form the plains, but also by its special tectonics. The section studied here is the Sahana of Bogota, especially in its southern part, which was mapped at 1:25.000. Stratigraphy of this region consists of a Cretacic of thousands of meters, from which, in the Sabana, only the upper part (the Guadalupe formation) outcrops, formed mainly by sandstones with 500-600 m. average thickness. Above the Guadalupe formation (coniacian to maestrichtian) lies the Guaduas formation (500-800 m.), which marks the transition from the cretacic marine conditions to the continental conditions belonging to the Tertiary. The Guaduas formation can be considered Maestrichtian to Paleocen. Above it is found a thick Tertiary sequence of about 3000 m., composed of the following formations: Cacho Sandstone, Bogota, La Regadera Sandstone and Usme; it looks like a continental sedimentation except during a short period in the Usme ( and perhaps in the La Regadera Sandstone! in which reappeared marine conditions. Finally, there are the Quaternarian deposits that have great importance and include lacustrine sediments, terraces, moraines, etc. The main part of the structures in the region of the Sabana are in the Guadalupe. In this respect, it is necessary to bear in mind that the Guadalupe formation is formed by a sequence of competent beds between incompetent beds, so the Guadalupe formation is the one which determines the structures in the whole region of the Sabanas. Structures of the region of the Sabana of Bogota are characterized by the following features: existence of wide synclines (mainly in the southern region, synclines of Fusagasugá and Usme) of simpler tectonics with their cores occupied by the Tertiary and between them Cretacic areas with tighter tectonics; anticlines which are always very narrow and extended; asymmetric character of the folds, E flanks of synclines (W of the anticlines) are steep, western flanks of the big synclines are soft; existence of overturned strata in the flanks of the folds, mainly located in the western flanks of the anticlines but also in the eastern ones; quite frequently the whole W flank of the anticlines is overturned and associated with longitudinal fult located in the Guadalupe-Guaduas contact. Another characteristic is the existence of some fan folds. If an ideal reconstruction of the crest is made, in almost every case there are very exaggerated shapes in the anticlines 'whose crets were eroded. Finally, it is necessary to point out the presence of salt domes. It is believed that in the formation of the Sabana structures the following agents were involved: action over the cover of basement tectonics; halocinesis; gravity; erosion destroying the anticline crest and with this the continuity of the strata. Basement tectonics is shown in the differentiation of the huge syncline area separated by higher areas and in the formation of a tectonics of coating in the cover. However, the tectonics of cover is not only controlled by the basement, halocinesis and gravity develop on it their own structures independent of the basement or produce special features in the coating structures. The Sabanas region is, of the whole “Cordillera Oriental”, the region in which the cover develops its own tectonics to the highest degree. The agents mentioned above work together and influence each other. Thus, the basement tectonics is mainly one of faults with their W sides sunken cutting a counterbalanced basement, dipping towards E; as a result the cover forms wide synclines with a soft W flank and an abrupt E flank (type Fusagasugá syncline), Gravity and halocinesis also determine the shape of the folds. Gravity makes an outstanding variety of structural variations. Structures originated by gravity or those in whose formation gravity was the main factor are: inversions in the flanks of the folds, produced by slide according to the dip of the strata originating at recumbent fold towards the de ressed part, folds in which the normal flank almost always has disappeared; faults by stretching and breaking with relation with the inverted limbs of the structures formed b the mechanism have been previously discussed; slide of groups of strata in normal position; accentuations by gravity of layers which were carried to a slightly inverse position by other mechanisms; formation of refolds of detail in a sequence which slides by gravity according to the dip; inversions produced by pressure of a mass which slides by gravity; horizontality of faults near the surface due to a collapse. From the indicated structures it can be deduced that in the Sabanas Region gravity acted principally to cause inversions. Halocinesis is another important phenomenon but its action can not be well defined because of lack of subsoil data. Basement Tectonics could have control in the liberation of the phenomena of saline injection; halocinesis could also locate certain flanks of the folds in adequate positions to develop gravitational structures. Finally, it is necessary to point out the effect of erosion, since early times erosion has been destroying the anticline crests and this fact has affected the other agents. It has effected halocinesis, giving rise to a discharge of pressure in anticline areas while the syncline areas build of by sedimentation. It has effected on the gravity, because erosion of the crests liberated the flanks so in them the gravitatory phenomena took place. Finally, because of the erosion of the crests continuity was broken in the Guadalupe formation in transversal direction to the structures, and the Guadalupe formation is the only important competent formation in the studied area. As a consequence, deformation in the last stages found special conditions because the ﬂanks could move independently one from the other and in certain cases the flanks of the anticlines acted as tops compressing the lutitic cores originating slight extrusions. The study of the Usme syncline allows us to know something about the temporary dimension of these structures. The Tertiary present a huge progressive discordance known to start in the Bogota formation and possibly in the Guaduas. Locally well marked angular unconformities are found. The movements which continue till the Quaternary may in part be due to the Salt Tectonics.